2003
DOI: 10.1108/01443570310476654
|View full text |Cite
|
Sign up to set email alerts
|

Vendor‐managed inventory and bullwhip reduction in a two‐level supply chain

Abstract: This paper compares the bullwhip properties of a Vendor Managed Inventory (VMI) supply chain with those of a traditional "serially-linked" supply chain. The emphasis of this investigation is the comparative impact the two structures have on the "Bullwhip Effect" generated. Particular attention is paid to the manufacturer's production ordering activities as demonstrated using a simulation model based on difference equations. Each of the four important sources of the Bullwhip Effect is documented and considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(116 citation statements)
references
References 35 publications
5
110
0
1
Order By: Relevance
“…They concluded that the appropriative delay depends on the level of aggregation and order scheduling. (Disney and Towill, 2003a) and (Disney and Towill, 2003b) produced two articles regarding VMI and the bullwhip effect. The first article demonstrates, through mathematical modeling and simulation that VMI helps to dampen the bullwhip effect focusing on that portion of the bullwhip effect created by what the authors term the "Forrester effect" (consisting of non-zero lead times and demand signaling processing).…”
Section: Discrete Event Simulationmentioning
confidence: 99%
“…They concluded that the appropriative delay depends on the level of aggregation and order scheduling. (Disney and Towill, 2003a) and (Disney and Towill, 2003b) produced two articles regarding VMI and the bullwhip effect. The first article demonstrates, through mathematical modeling and simulation that VMI helps to dampen the bullwhip effect focusing on that portion of the bullwhip effect created by what the authors term the "Forrester effect" (consisting of non-zero lead times and demand signaling processing).…”
Section: Discrete Event Simulationmentioning
confidence: 99%
“…Table 1.1 contains the simulation results for the non-transport performance measures. It can be seen that VMI delivers consistently lower levels of demand amplification than the traditional scenario, findings that are in line with those reported by Disney and Towill (2003). In both scenarios the level of amplification is independent of the vehicle capacity.…”
Section: Vmi and Transport: Simulation Studysupporting
confidence: 80%
“…Disney and Towill (2003c) report that the concept was initially discussed by Magee (1958), in a presentation of a conceptual framework for designing a production control system, pointed by the authors as the pioneer model of Vendor Managed Inventory. Two years later, the publication of Clark and Scarf (1960) Dejonckheere et al 2004, Disney et al 2004a, Geary et al 2006, Towill et al 2007, Disney and Lambrecht 2008.…”
Section: Methodological Approach and Mathematical Formalismmentioning
confidence: 99%